Coco : my delicious life - May, Kyla. (New York, N.Y. : Scholastic Inc., 2013)
Coco, one of the Lotus Lane Girls, loves cooking and animals, so when the club decides to plant a vegetable garden to help save snails, organizing a cupcake sale is an obvious idea--but Mika, the new girl next door, is still an unresolved problem. Includes cupcake recipe.
"Branches.".
740
Keywords: Baking -- Juvenile fiction; Gardening -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Neighbors -- Juvenile fiction; Elementary schools -- Juvenile fiction; Baking -- Fiction; Gardening -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Neighbors -- Fiction; Elementary schools -- Fiction; Schools -- Fiction; Diaries -- Fiction; Baking -- Fiction; Gardening -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Neighbors -- Fiction; Elementary schools -- Fiction; Schools -- Fiction; Diaries -- Fiction; Diary fiction